2014
DOI: 10.1186/2193-1801-3-156
|View full text |Cite
|
Sign up to set email alerts
|

The physico-chemical properties and biostimulative activities of humic substances regenerated from lignite

Abstract: The positive effect of humic acids on the growth of plant roots is well known, however, the mechanisms and role of their physical structure in these processes have not been fully explained yet. In this work, South-Moravian lignite was oxidized by means of nitric acid and hydrogen peroxide to produce a set of regenerated humic acids. The elemental composition, solid state stability and solution characteristics were determined and correlated in vitro with their biological activity. A modified hydroponic method w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 39 publications
(63 reference statements)
1
6
0
2
Order By: Relevance
“…Plants respond to abiotic stresses through both physiological and morphological responses ( Yadav et al, 2020 ). Many of these same responses, for example, physiological responses like increases in [Ca 2+ ] cyt ( Ramos et al, 2015 ), increased production of antioxidants ( Moghadam et al, 2014 ; Hemida et al, 2017 ), and morphological changes to root system architecture ( Canellas et al, 2008 , 2009 , 2010 ; Bobik et al, 2010 ; Canellas et al, 2012 ; Aguiar et al, 2009 , 2013 ; Dobbss et al, 2010 ; Muscolo et al, 2010 ; David et al, 2014 ; Garcia et al, 2016 ; van Tol de Castro et al, 2021 ) have also been observed in plants treated with HS. Plants exposed to abiotic stress typically develop recognizable morphological changes, called stress-induced morphogenesis responses (SIMS), to root systems that include re-differentiation of the pericycle and formation of lateral roots, inhibition of root cell elongation, formation of root hairs in the apex, and blocked cell division in the primary meristem ( Patakas, 2011 ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Plants respond to abiotic stresses through both physiological and morphological responses ( Yadav et al, 2020 ). Many of these same responses, for example, physiological responses like increases in [Ca 2+ ] cyt ( Ramos et al, 2015 ), increased production of antioxidants ( Moghadam et al, 2014 ; Hemida et al, 2017 ), and morphological changes to root system architecture ( Canellas et al, 2008 , 2009 , 2010 ; Bobik et al, 2010 ; Canellas et al, 2012 ; Aguiar et al, 2009 , 2013 ; Dobbss et al, 2010 ; Muscolo et al, 2010 ; David et al, 2014 ; Garcia et al, 2016 ; van Tol de Castro et al, 2021 ) have also been observed in plants treated with HS. Plants exposed to abiotic stress typically develop recognizable morphological changes, called stress-induced morphogenesis responses (SIMS), to root systems that include re-differentiation of the pericycle and formation of lateral roots, inhibition of root cell elongation, formation of root hairs in the apex, and blocked cell division in the primary meristem ( Patakas, 2011 ).…”
Section: Discussionmentioning
confidence: 92%
“…Plants exposed to abiotic stress typically develop recognizable morphological changes, called stress-induced morphogenesis responses (SIMS), to root systems that include re-differentiation of the pericycle and formation of lateral roots, inhibition of root cell elongation, formation of root hairs in the apex, and blocked cell division in the primary meristem ( Patakas, 2011 ). In many reports, application of HA has resulted in increases in numbers of lateral roots, lateral root length, and density ( Aguiar et al, 2009 ; Canellas et al, 2009 , 2010 , 2011 , 2012 ; Dobbss et al, 2010 ; Muscolo et al, 2010 ; Aguiar et al, 2013 ; David et al, 2014 ; Garcia et al, 2016 ; van Tol de Castro et al, 2021 ). However, in some cases, increases in lateral roots have been accompanied by increases in the principal root length ( Aguiar et al, 2009 ; Canellas et al, 2009 ; van Tol de Castro et al, 2021 ), root diameter ( Aguiar et al, 2013 ; Garcia et al, 2016 ), or both ( Canellas et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…A low molecular weight fraction of HS from leonardite enhanced the seedling's, root surface area, root length, and total root number of snap bean (Qian et al 2015). David et al (2014) demonstrated that potassium humate salts extracted from lignite, and potassium humate regenerated from lignite with two oxidizing agents (nitric acid and hydrogen peroxide), positively influenced root growth and division, starch and protein contents in treated Zea mays seedlings.…”
Section: Introductionmentioning
confidence: 87%
“…They are a dark brown natural organic compounds, ubiquitous in water, soil, and sediments (Piccolo, 2002). Particularly, leonardite, originating from the atmospheric oxidation of lignite, is very rich in humic acids (David et al, 2014). Leonardite application has been shown to improve nutrient uptake, such as Fe, N, and K, and increase plant yield and quality (Ece et al, 2007;Fascella et al, 2015;Cieschi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%